2019
DOI: 10.3389/fpls.2019.00143
|View full text |Cite
|
Sign up to set email alerts
|

Biofortification of Six Varieties of Lettuce (Lactuca sativa L.) With Iodine and Selenium in Combination With the Application of Salicylic Acid

Abstract: The agrotechnical methods of biofortification of plants, i.e., enriching them in iodine (I) and selenium (Se) could be effective methods to enrich food products in these elements. The advantage of agrotechnical methods of biofortification is the incorporation of elements in organic compounds in plants; therefore, they have better health-promoting properties than pure technical salts. Two-year studies were conducted in a greenhouse with hydroponic cultivation of three botanical varieties of lettuce in an NFT (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…Consequently, the RDA-Se varies with the same trend reaching a peak at 40 µM dose in both cultivars (685 and 646%, respectively for the green and red Salanova, respectively). Our RDA-Se values observed at the lowest Se dose (8 µM), were comparable with those found by Smoleń et al (2019) on six varieties of lettuce biofortified with selenium combined with iodine at the 6.3 µM Se dose. Particularly, the iceberg varieties Krolowa and Maugli showed the lowest values (23.8 and 27.1%, respectively), while the green butterhead Cud Voorburgu and the red lettuce Lollo rossa reached the highest percentage (44.7 and 44.8%, respectively) which were comparable with the values found in green and red Salanova at the 8 µM Se dose (57 and 45%, respectively).…”
Section: Resultssupporting
confidence: 88%
“…Consequently, the RDA-Se varies with the same trend reaching a peak at 40 µM dose in both cultivars (685 and 646%, respectively for the green and red Salanova, respectively). Our RDA-Se values observed at the lowest Se dose (8 µM), were comparable with those found by Smoleń et al (2019) on six varieties of lettuce biofortified with selenium combined with iodine at the 6.3 µM Se dose. Particularly, the iceberg varieties Krolowa and Maugli showed the lowest values (23.8 and 27.1%, respectively), while the green butterhead Cud Voorburgu and the red lettuce Lollo rossa reached the highest percentage (44.7 and 44.8%, respectively) which were comparable with the values found in green and red Salanova at the 8 µM Se dose (57 and 45%, respectively).…”
Section: Resultssupporting
confidence: 88%
“…Hydroponics or soilless is another technological approach providing strict control of crop growing conditions and minimizing the effect of environmental factors. Four studies of joint Se–I biofortification in soilless conditions [ 38 , 39 , 40 , 41 ] demonstrated the stimulating effect of salicylic acid on I accumulation. Furthermore, in conditions of joint Se–I hydroponics application, the activation of Se organic forms biosynthesis (SeMet, SeCys) reportedly takes place [ 38 , 41 ].…”
Section: Different Technological Approachesmentioning
confidence: 99%
“…In the NFT hydroponic system, target replanting was preceded by thorough rinsing of the substrate between the seedlings' The type of nutrient solution, its preparation (content of macro-and microelements), regulation of pH and EC, and type of fertilizers in the NFT were the same as in our previous studies with lettuce in the same hydroponic system (Smoleń et al, 2019b). The I used in the base nutrient solutions (control) was iodide I − (25.52 µg I•dm −3 ) and iodate IO 3 − (0.29 µg I•dm −3 ).…”
Section: Plant Materials and Treatmentsmentioning
confidence: 99%